Cost-Effectiveness of Nivolumab Plus Chemotherapy vs. Chemotherapy as First-Line Treatment for Advanced Gastric Cancer/Gastroesophageal Junction Cancer/Esophagel Adenocarcinoma in China - Shu, Yamin; Ding, Yufeng; Zhang, Qilin (Frontiers in Oncology, 2022)
Objective: The purpose of this study was to evaluate the cost-effectiveness of nivolumab plus chemotherapy vs chemotherapy as fist-line therapy in patients with advanced gastric cancer/gastroesophageal junction cancer/oesophageal adenocarcinoma from the perspective of Chinese healthcare system. Methods: This economic evaluation used a state-transition Markov model to assess the cost and effectiveness of nivolumab plus chemotherapy vs chemotherapy as firstline treatment for advanced gastric cancer/gastroesophageal junction cancer/oesophageal adenocarcinoma. The characteristics of patients in the model came from a phase 3, open-label randomized clinical trial (CheckMate 649). Key clinical data were based on the CheckMate 649 trial conducted from March 2017 to April 2019, and costs and utilities were collected from the published literatures. Total cost of treatment per patient, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) were calculated for the two treatment strategies. Deterministic sensitivity analysis and probabilistic sensitivity analysis were performed. Results: In the baseline analysis, the incremental effectiveness and cost of nivolumab plus chemotherapy vs chemotherapy were 0.28 QALYs and $78,626.53, resulting in an ICER of $278,658.71/QALY, higher than the willingness-to-pay (WTP) threshold of China ($31,498.70/QALY). The model was sensitive to the duration of PFS for nivolumab plus chemotherapy group, the cost of nivolumab per 100 mg and the utility of PFS. Conclusion: Nivolumab plus chemotherapy was clearly not a cost-effective treatment strategy compared with chemotherapy as fist-line therapy for patients with advanced gastric cancer/gastroesophageal junction cancer/oesophageal adenocarcinoma in China. Reducing the price of nivolumab may improve the cost-effectiveness.